Integrating Technology in Physical Education: A Systematic Review of Pedagogical Innovations and Student Engagement - Haibat B.Patil, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The integration of technology into physical education (PE) represents a transformative shift in pedagogical practices, enabling educators to enhance student engagement, personalize learning, and promote lifelong fitness habits. This systematic review explores the range and impact of technological innovations implemented in PE settings, with particular emphasis on their influence on teaching methods and student outcomes. Drawing upon peer-reviewed literature published between 2010 to 2024, the review examines how tools such as wearable fitness trackers, mobile applications, video analysis software, virtual and augmented reality (VR/AR), and online learning platforms have been used to support both theoretical and practical components of PE curricula. The findings suggest that technology can significantly improve student motivation, participation, and performance by providing real-time feedback, fostering autonomy, and gamifying physical activities. Wearables allow for individualized monitoring, mobile apps offer customized workouts, and video tools support technical skill analysis. VR/AR applications simulate immersive training scenarios, while learning management systems (LMS) extend learning beyond the gymnasium.This review underscores the pedagogical potential of technology in modern PE and advocates for strategic implementation to maximize its educational benefits. Recommendations for future research include longitudinal studies and the development of evidence-based frameworks for sustainable technology integration in PE.